Black Society Trilogy - Miike, Takashi; Imaizumi, Naosuke; Li Yi-Hsu; Caesar, Takeshi; Aikawa, Sho; Itou, Yukjie (Arrow Video, 2017)
After several years spent working almost exclusively in the direct-to-video world of "V-cinema" in Japan, Takashi Miike announced himself as a world-class filmmaking talent with this trio of thematically-connected, character-centric crime stories about violence, the underworld of Japanese society, families both real and surrogate, and the possibly hopeless task of finding one's place in the world. His first films made specifically for theatrical release, and his first for a major studio, the "Black Society Trilogy" was the beginning of Miike's mature career as a filmmaker and they remain among the prolific director's finest works. [www.arrowfilms.co.uk]
Keywords: Blu-Ray-Disc